Analysis of the Efficiency of Financial Groups in Ecuador. A Non-Parametric Proposal Based on Data Envelopment Analysis in Two Stages - Villarreal Satama, Freddy Lenin (2022)
The objective of this paper is to analyze the efficiency of financial groups in Ecuador in the period 2015-2021, through the non-parametric methodology of DEA Data Envelopment Analysis, under the two-stage enveloping technique. The data was obtained from the database of the Superintendence of Banks of Ecuador whose main results show that, of the five financial groups analyzed, three of them present 100% efficiency in all periods and two of them are inefficient because the opportunity arises. to generate substantial improvements through the technical comparison of the input and output variables such as operating expenses, mainly fixed assets that allow them to improve in the medium term.